Pengaruh Motivasi Dan Gaya Kepemimpinan Terhadap Kinerja Perangkat Desa Di Kecamatan Pace Kabupaten Nganjuk : (Studi Kasus Di Desa Cerme, Desa Mlandangan, Desa Pace Kulon, Desa Pace Wetan, Desa Babadan. Desa Gondang, Desa Joho, Desa Jampes Kecamatan PaceKabupaten Nganjuk) - Yusnandar, Impi; IGG Heru Marwanto; Djunaedi; Budi Rahayu (Universitas Indo Global Mandiri, 2023)
The purpose of this study is to dertemine the degree to which motivation affects performance of village officials and village staff and to find out how much in fluence the village heads manner of leadership has on performance in the wokers’ environment at the village office, especially in ieght village in Pace District, Nganjuk Regency and to find out how much influence motivation and leadership style together on the performance of village devices and staff. The recearh method used is a qualitative method with and explanatory and inference descriptive approach, using a questionnaire as atool for data collection Isaac and Micchael’s formula, with and error rate 5 % . Alst analysis used is correlation regresion. From the result of annalysis the make method of in the in fluence of motivation on the performance of village official and staff is determainded by dthe dimension of motives, expectations and incentives of 31.6%, other factors that affect physiological needs and the need for appriciasion. Respect and trust for subordinates ideas, take into consider the emotions of subordinates pay attention the convenience of labor on behalf of subordinates, take taking the component into consideration of work satisfaction for subordiantes in completing tasks entrusted to them an recognition of the status of subordinates appropriately and profesionaly by 16,4 %, the factor other that affect inttelegence, social, mature, and wide social relations, personal initiative and drive for achievement and attitudes of human relation of 33,44 other factors that affect the quantity, quality, effectiveness and independence. Keywords: motivation, leadership, performance